2021
DOI: 10.3390/en14248443
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Environmental Protection Expenditures in EU Countries

Abstract: Environmental protection policy is a widely discussed issue in scientific works. However, special attention should be also paid to the effectiveness of expenditures on environmental protection, and this is the main goal of this paper. The countries of the European Union were selected for this analysis due to the fact that, in recent years, this region has become an informal world leader with respect to the implementation of policy measures in the field of environmental protection. For that reason, the data env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 124 publications
(152 reference statements)
0
4
0
Order By: Relevance
“…It aimed to harmonize energy production regulations and to establish the same competences for national regulators. Environmental goals also play a significant role in the EU's energy policy and require technological development with the increasing use of renewable energy sources [2,3]. At the same time, market demonopolization and liberalization are becoming priorities of EU energy policy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It aimed to harmonize energy production regulations and to establish the same competences for national regulators. Environmental goals also play a significant role in the EU's energy policy and require technological development with the increasing use of renewable energy sources [2,3]. At the same time, market demonopolization and liberalization are becoming priorities of EU energy policy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide emissions per capita (natural log), (excluding LULUCF * , tonnes of CO 2 equivalent) OECD This is a variable applied as a proxy for environmental degradation (Hatmanu et al, 2022). Scholars examined the ties between government expenditures on environmental protection and environmental quality (emissions of pollutants) (Barrell et al, 2021;Halkos & Paizanos, 2014;Donkor et al, 2022;Wójtowicz et al, 2022). Barrell et al (2021) confirmed the problem of deteriorating efficiency of environmental expenditures across the selected EU countries.…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…Scholars examined the ties between government expenditures on environmental protection and environmental quality (emissions of pollutants) (Barrell et al, 2021;Halkos & Paizanos, 2014;Donkor et al, 2022;Wójtowicz et al, 2022). Barrell et al (2021) confirmed the problem of deteriorating efficiency of environmental expenditures across the selected EU countries. Donkor et al (2022) found both positive and negative influence of government finance expenditures on environmental quality in different countries.…”
Section: Co 2 Emissionsmentioning
confidence: 99%
See 1 more Smart Citation